Il Principe felino e il tabù dell’incesto nel Gattopardo - Sabato, Adriana (L'ospite ingrato, 2022)
The essay suggests a hermeneutic concept related to the word “danger”, that emerges in The Leopard’s mind when he knows about a possible marriage between his daughter Concetta and his nephew Tancredi. Starting from the cryptic novel substrate, influenced by Sigmund Freud psychoanalytic theory, the analysis focuses on the unveiling of the ancient and primordial roots of the aristocrat protagonist, characterised as animal- like, roots anchored to totemic culture, to inviolable and inexpressible taboos.